Haemorrhagic snake venom metalloproteases and human ADAMs cleave LRP5/6, which disrupts cell–cell adhesions in vitro and induces haemorrhage in vivo. (20th April 2017) - Seo, Tadahiko; Sakon, Taketo; Nakazawa, Shiori; Nishioka, Asuka; Watanabe, Kohei; Matsumoto, Kaori; Akasaka, Mari; Shioi, Narumi; Sawada, Hitoshi; Araki, Satohiko
Abstract : Snake venom metalloproteases (SVMPs) are members of the a disintegrin and metalloprotease (ADAM) family of proteins, as they possess similar domains. SVMPs are known to elicit snake venom‐induced haemorrhage; however, the target proteins and cleavage sites are not known. In this work, we identified a target protein of vascular apoptosis‐inducing protein 1 (VAP1), an SVMP, relevant to its ability to induce haemorrhage. VAP1 disrupted cell–cell adhesions by relocating VE‐cadherin and γ‐catenin from the cell–cell junction to the cytosol, without inducing proteolysis of VE‐cadherin. The Wnt receptors low‐density lipoprotein receptor‐related proteins 5 and 6 (LRP5/6) are known to promote catenin relocation, and are rendered constitutively active in Wnt signalling by truncation. Thus, we examined whether VAP1 cleaves LRP5/6 to induce catenin relocation. Indeed, we found that VAP1 cleaved the extracellular region of LRP6 and LRP5. This cleavage removes four inhibitory β‐propeller structures, resulting in activation of LRP5/6. Recombinant human ADAM8 and ADAM12 also cleaved LRP6 at the same site. An antibody against a peptide including the LRP6‐cleavage site inhibited VAP1‐induced VE‐cadherin relocation and disruption of cell–cell adhesions in cultured cells, and blocked haemorrhage in mice in vivo . Intriguingly, animals resistant to the effects of haemorrhagic snake venom express variants of LRP5/6 that lack the VAP1‐cleavage site, or low‐density lipoprotein receptor domain class A domains involved in formation of the constitutively active form. The results validate LRP5/6 as physiological targets of ADAMs. Furthermore, they indicate that SVMP‐induced cleavage of LRP5/6 causes disruption of cell–cell adhesion and haemorrhage, potentially opening new avenues for the treatment of snake bites. Abstract : The targets of a disintegrin and metalloprotease (ADAM)‐type proteases in haemorrhagic snake venom and in invasive pseudopodia of human leukocytes and cancer cells are unclear. Here we show that snake haemorrhagic metalloproteases and human ADAMs cleave low‐density lipoprotein receptor‐related proteins 5 and 6 (LRP5/6), which mediate disruption of cell–cell adhesions and haemorrhage. LRP5/6 are proposed to be receptors of ADAMs, functioning as cell barrier openers.